Carbon fiber-reinforced PEEK in implant dentistry: A scoping review on the finite element method. Issue 12 (6th October 2021) - Souza, Júlio C. M.; Pinho, Sofia S.; Braz, Maria Pranto; Silva, Filipe S.; Henriques, Bruno
Abstract: Objective : The aim of the present study was to perform an integrative systematic review on the stress distribution assessed by finite element analysis on dental implants or abutments composed of carbon fiber-reinforced PEEK composites. Method: An electronic search was performed on PUBMED and ScienceDirect using a combination of the following search terms: PEEK, Polyetheretherketone, FEA, FEM, Finite element, Stress, Dental implant and Dental abutment. Results: The findings reported mechanical properties and the stress distribution through implant and abutment composed of PEEK and its fiber-reinforced composites. Unfilled PEEK revealed low values of elastic modulus and strength that negatively affected the stress distribution through the abutment and implant towards to the bone tisues. The incorporation of 30% carbon fibers increased the elastic modulus and strength of the PEEK-matrix composites although some studies reported no statistic differences in stress magnitude when compared to unfilled PEEK. However, an increase in short carbon fibers up to 60% revealed an enhancement on the stress distribution through abutment and implants towards to the bone tissues. PEEK veneering onto titanium core structures can also be a strategy to control the stress distribution at the implant-to-bone interface. Conclusions: The stiffness and strength of PEEK-matrix composites can be increased by the improvement of the carbon fibers' network. Thus, the content, shape, dimensions, and chemical composition of fibers are key factors to improve the stress distribution through abutment and implants composed of PEEK-matrix composites.